Epidemiological Profile of Infectious Diseases Notified in a Municipality Integrated into the Bioceanic Route in Brazil - Paloma Almeida Kowalski; João Pedro Arantes da Cunha; Emily Ruiz Cavalcante; Rachel Carvalho Lemos; Mariana Pavão de Araújo Gemperli Zatti; Fabiana Moreira Coutinho; Jordão Raphael Fujii Ramos; Gabriela Felix Dias Lima; Guilherme Hideo da Costa Ota; Aline Cabral Lira; Rafael Vilela de Campos (Archives of Current Research International, 2021)
Introduction: The Bioceanic Routeand its economic integration will have tremendous impact within the cities under management. The state of Mato Grosso do Sul and interior municipalities of the Paraguay-Brazil Border are standouts. The permanence of these workers in Brazilian territory will lead to a rapid increase in population in the border towns connected by the corridor and consequently, in the incidence of infectious diseases. Methods: This is a cross-sectional, quantitative and descriptive study of documentary approach that aimed to analyze the prevalence of tropical infectious diseases such asarboviroses and Diseases Related to Inadequate Environmental Sanitation (DRIES) notified and stored in the National System of Notifiable Diseases (SINAN). The sample consisted of new cases of these pathologies in the municipality of Porto Murtinho registered between January 2017 and December 2020. Results: Within the period analyzed, an increase of 10% in the total number of diseases occured. The number of dengue cases increased 36 times its previous rates; there was a maintenance from cases of Leptospirosis, Yellow Fever, Zika, Chikungunya, whereas the incidence of Syphilis, HIV and HPV decreased. Conclusions: Actions aimed at preventing the increase of Arboviruses and DRIESI before, during and after the construction of the Bioceanic Route are needed in view of the changes that will be imposed by it. Faced with the increase in the flow of people that is inevitable with the construction of this project, several outcomes are expected based on previous experiences already mentioned in this work.